A modified Delphi consensus on creating a time-clocked care pathway in severe asthma – time is of the essence - M. Bhutani; T. Winders; D. Price; GW Canonica; JC in ‘t Veen; M. Kupczyk; A. Evans; S. Patel; JWH Kocks (npj Primary Care Respiratory Medicine, 2026)
Abstract Severe asthma (SA) affects approximately 10% of the global asthma population. Symptoms and exacerbations lead to reduced quality of life and increased hospitalisations. Patients with uncontrolled disease often experience increased risks due to delays in referral, assessment, and treatment initiation. The aim of this study was to establish multinational consensus on the preferred approach to time-clocked care in the management of SA from primary through to specialist care. A modified Delphi methodology was used. A steering committee convened and developed 63 consensus statements across five key topics related to SA diagnosis, referral, and management. The statements were created into a four-point Likert scale online survey and distributed to healthcare professionals experienced in SA care across five countries. The threshold for consensus was set at 75%. Responses were collated anonymously, and 500 responses were received from across France, Germany, Italy, Spain, and the United States. The majority had ≥ five years of experience in role. Consensus was achieved for 53/63 statements (85%). There was agreement on the necessity of timely SA care, with 95% of respondents supporting that time-clocked care is essential. An aspirational 18-week target from referral to implementation of care, including biologic therapy initiation, was established. Based on these findings, a SA care timeline was proposed. This consensus provides an aspirational framework for improving the SA care pathway from primary through to specialist care. Implementing the timeline into local health systems is hoped to facilitate earlier referral, treatment initiation, and follow-up to improve patient outcomes.